PO145 Strange rheuminations. (1st December 2017) - Ward, V; Parsons, G; Buchanan, S; Grote, H; Dahdelah, S; Farmer, S; Grieve, J; Jaunmuktane, Z; Shah, S; Isenberg, D; Zandi, M; Gandhi, S
Abstract : Pachymeningitis is a rare condition comprising fibrous thickening of the dura mater which may lead to mass effect and neurovascular compromise. Causes include infection, malignancy and autoimmunity; rarely it can arise as a serious complication of Rheumatoid Arthritis, with mortality approaching 50% when untreated. In this latter group, it can arise with no evidence of active synovitis and can present with transient neurological deficits. Particular vigilance is required in patients exposed to anti-TNF-α therapies as both new and relapsed cases have been identified in patients exposed. We present a 72-year-old woman with well-controlled Rheumatoid Arthritis on Etanercept therapy, who experienced transient discrete episodes of expressive dysphasia and left-sided neglect on a background of progressive cognitive decline. MRI imaging revealed meningeal thickening and enhancement. CSF examination identified pleocytosis with raised protein and further studies excluded infection and malignancy. Rheumatological assessment confirmed quiescent disease. Necrotising granulomas and evidence of a vasculitis were elicited on meningeal biopsy, prompting high-dose steroid treatment which yielded improvement. Subsequent body imaging, however, demonstrated splenic and renal infarcts necessitating Rituximab therapy. Pachymeningitis should be considered in patients with well-controlled Rheumatoid Arthritis presenting with transient neurological deficits.